2008
DOI: 10.1074/jbc.m710518200
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor Cylindromatosis Acts as a Negative Regulator for Streptococcus pneumoniae-induced NFAT Signaling

Abstract: Gram-positive bacterium Streptococcus pneumoniae is an important human pathogen that colonizes the upper respiratory tract and is also the major cause of morbidity and mortality worldwide. S. pneumoniae causes invasive diseases such as pneumonia, meningitis, and otitis media. Despite the importance of pneumococcal diseases, little is known about the molecular mechanisms by which S. pneumoniae-induced inflammation is regulated, especially the negative regulatory mechanisms. Here we show that S. pneumoniae activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…It is worthy to note that the NFAT, NF-kB, and STAT3 pathways shown in this study to be regulated by RCAN1 are universally important during respiratory tract infections and have been extensively studied during Pneumococcus infection (64)(65)(66). Thus, it is likely that the phenotype observed in RCAN1-deficient animals may not be specific to P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 92%
“…It is worthy to note that the NFAT, NF-kB, and STAT3 pathways shown in this study to be regulated by RCAN1 are universally important during respiratory tract infections and have been extensively studied during Pneumococcus infection (64)(65)(66). Thus, it is likely that the phenotype observed in RCAN1-deficient animals may not be specific to P. aeruginosa infection.…”
Section: Discussionmentioning
confidence: 92%
“…These include activation of immune and inflammatory cells via interaction of pneumolysin with Toll-like receptor 4 [3], as well as by induction of Ca 2+ influx, particularly into phagocytes and epithelial cells, as a consequence of sublytic action of the toxin [4,5]. In both cases, this results in activation of intracellular signalling cascades, which trigger the synthesis of a range of pro-inflammatory neutrophil-and monocyte/macrophage-activating chemokines/cytokines [6][7][8].…”
mentioning
confidence: 99%
“…Previous studies using murine systems or immortalized human T cells suggested that CYLD might undergo proteolytic cleavage upon activation (25,26,57). Since productive HIV infection requires T cell activation, we tested whether CYLD was cleaved in primary human CD4 ϩ T cells.…”
Section: Cyld Is Highly Expressed In Primary Cd4mentioning
confidence: 99%
“…Several molecules regulating this pathway (e.g., NEMO, TRAF2, TAK1, and TRAF6) are substrates of CYLD (7,8,14,23,24). Moreover, CYLD itself has been proposed to act as a negative regulator of the NFAT pathway (25,26).…”
mentioning
confidence: 99%